COVID-19 EFFECT IN SOCIETY AND GOVERMENT - Muhammmad Supriyadi; Danisa Salsabila; Sephiala Riztianendra (Universitas Duta Bangsa Surakarta, 2020)
In indonesia, the underlying cause is a government that is seen as sluggish and ill-advisedin dealing with the corona epidemic. Government policy to implement a lockdown system leads tocritics or deals with